Description of Junior High School Students’ Mathematical Understanding According to Skemp Theory in terms of Rational Personality Types - Rachmawati, Intan; Subanti, Sri; Usodo, Budi (JTAM (Jurnal Teori dan Aplikasi Matematika), 2023)
Mathematical understanding is one of the supporting factors for students' success in mathematics. Skemp divides understanding into two types, namely instrumental understanding and relational understanding. This research purpose was to describe the mathematical understanding of seventh grade D students in solving set problems based on Skemp's theory of understanding in terms of rational personality types. The type of research used was descriptive qualitative. This research was conducted at Junior High School Darul Aman Mataram of 2021/2022 academic year. Selection of subjects using a purposive sampling technique. The subjects in this study were two students with rational personality types. Data were obtained using a mathematical understanding test and interviews. The study's results showed that students with rational personality types tend to have a relational understanding because they can explain reasons or interpret problem-solving procedures according to the set concept correctly. In addition, students are able to understand the purpose of the given set of problems, can apply ideas according to the logic of thinking in solving problems, can write problem solving procedures coherently according to Skemp's theory even though they tend to be brief, can solve mathematical understanding problems accompanied by appropriate answer arguments, can change mathematical sentences in the given problem in the form of words, images, or certain mathematical symbols. Furthermore, this type can achieve all of the indicators of instrumental understanding and can fulfill the six indicators of relational understanding, except for the ability to correlate several set concepts. Based on these results, it is expected that rational personality type students can determine detailed planning in solving problems, and improve understanding of mathematical concepts such as being more careful in the use of solution strategies so that students are accustomed to applying various solution strategies.